Grenada. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Granada during 2021 are identified, with respect to the needs and interests of the country, strengthening issues such as resilience to climate change, food safety, composting, agrotourism, bioeconomy, regenerative agriculture, land and water use, livestock management and quality forage. Likewise, work was done to strengthen exports and improve plant nutrition. Finally, collaboration was provided in the training of rural youth in agricultural matters and pest control.